Efficacy and ototoxicity of different cyclodextrins in Niemann–Pick C disease. Issue 5 (20th April 2016) - Davidson, Cristin D.; Fishman, Yonatan I.; Puskás, István; Szemán, Julianna; Sohajda, Tamás; McCauliff, Leslie A.; Sikora, Jakub; Storch, Judith; Vanier, Marie T.; Szente, Lajos; Walkley, Steven U.; Dobrenis, Kostantin
Abstract: Objective: Niemann–Pick type C (NPC) disease is a fatal, neurodegenerative, lysosomal storage disorder characterized by intracellular accumulation of unesterified cholesterol (UC) and other lipids. While its mechanism of action remains unresolved, administration of 2‐hydroxypropyl‐ β ‐cyclodextrin (HP β CD) has provided the greatest disease amelioration in animal models but is ototoxic. We evaluated other cyclodextrins (CDs) for treatment outcome and chemical interaction with disease‐relevant substrates that could pertain to mechanism. Methods: NPC disease mice treated for 2 weeks with nine different CDs were evaluated for UC, and GM2 and GM3 ganglioside accumulation using immunohisto/cytochemical and biochemical assays. Auditory brainstem responses were determined in wild‐type mice administered CDs. CD complexation with UC, gangliosides, and other lipids was quantified. Results: Four HP β CDs varying in degrees of substitution, including one currently in clinical trial, showed equivalent storage reduction, while other CDs showed significant differences in relative ototoxicity and efficacy, with reductions similar for the brain and liver. Importantly, HP γ CD and two sulfobutylether‐CDs showed efficacy with reduced ototoxicity. Complexation studies showed: incomplete correlation between CD efficacy and UC solubilization; an inverse correlation for ganglioside complexation; substantial interaction with several relevant lipids; and association between undesirable increases of UC storage in Kupffer cells and UC solubilization. Interpretation: CDs other than HP β CD identified here may provide disease amelioration without ototoxicity and merit long‐term treatment studies. While direct interactions of CD‐UC are thought central to the mechanism of correction, the data show that this does not strictly correlate with complexation ability and suggest interactions with other NPC disease‐relevant substrates should be considered.